ULAMA BERBAGI OTORITAS: Fungsi dan Peran MUI Kota Padanmgsidimpuan dalam meningkatkan kesadaran dan budaya hukum masyarakat - AHMATNIJAR, AHMATNIJAR (TAZKIR: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2016)
Authority relating to the influence of a person, authority, command, control others, giving rise to voluntary submission. Authorities of MUI Padangsidimpuan in running theoretically function is as a container deliberation, silaturrahmi the scholars, zuama and Muslim scholars in protecting the people, develop and practice the teachings of Islam, raising ukhuwah Islamiyah in Islamic life. As an organization representing Muslims in the relationship and inter-religious consultations and giving fatwas to the Muslims and the government, whether requested or not requested. Authorities of MUI Padangsidimpuan deals with globalization, liberalization, institutions that have authority, other Islamic religious social organizations. For that function should be developed according to the quality and quantity of life issues are growing. While the role of the practically had to share authority with the agency that has the authority and the authority created pure, so the authority was scattered and functioned by other institutions. In many ways, the authority of MUI Padangsidimpuan more focused on efforts to improve the legal awareness of society, then a new lead on efforts to improve the legal culture of society.